2009
DOI: 10.1007/s00330-009-1538-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis between benign and malignant gallbladder diseases with real-time contrast-enhanced ultrasound

Abstract: The value of contrast-enhanced ultrasound (CEUS) in differential diagnosis between benign and malignant gallbladder diseases was investigated. Thirty-three patients with gallbladder carcinomas and 47 with benign gallbladder diseases underwent CEUS. The lesion enhancement time, enhancement extent, pattern, dynamic change of enhancement and the intactness of gallbladder wall were evaluated. In the early phase at CEUS, hyper-, iso-, hypo-, and non-enhancement were found in 84.8% (28/33), 9.1% (3/33), 6.1% (2/33),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
127
1
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(148 citation statements)
references
References 21 publications
(39 reference statements)
4
127
1
10
Order By: Relevance
“…Gallbladder and bile duct: Conventional gray-scale US is the first-line imaging investigation for diagnosis of gallbladder diseases, but can result in difficulty in determining the nature of the gallbladder lesions in some cases, especially in differentiating chronic cholecystitis with thickened wall from gallbladder carcinoma with thickened wall or in differentiating motionless sludge from gallbladder cancer [23,24] . Xie et al [23] evaluated the usefulness of CEUS in diagnosing gallbladder diseases.…”
Section: Ceusmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallbladder and bile duct: Conventional gray-scale US is the first-line imaging investigation for diagnosis of gallbladder diseases, but can result in difficulty in determining the nature of the gallbladder lesions in some cases, especially in differentiating chronic cholecystitis with thickened wall from gallbladder carcinoma with thickened wall or in differentiating motionless sludge from gallbladder cancer [23,24] . Xie et al [23] evaluated the usefulness of CEUS in diagnosing gallbladder diseases.…”
Section: Ceusmentioning
confidence: 99%
“…Xie et al [23] evaluated the usefulness of CEUS in diagnosing gallbladder diseases. They found that characters such as hyperenhancement or isoenhancement in the early phase and then fading out to hypoenhancement, as well as destruction of the gallbladder wall intactness, are more frequent in malignancy.…”
Section: Ceusmentioning
confidence: 99%
“…W początko-wym okresie są niedostrzegane lub bagatelizowane [2,4,7,9]. Najczęściej podawane dolegliwości wiążą się ze współistniejącą w większości przypadków kamicą pęcherzyka.…”
Section: Introductionunclassified
“…Najczęściej podawane dolegliwości wiążą się ze współistniejącą w większości przypadków kamicą pęcherzyka. Ataki kolki wątrobowej są jednak rzadkie, zwykle są to dolegliwości o typie rozpierania, uczucia dyskomfortu w prawym górnym kwadrancie jamy brzusznej [2,6,9]. Mają one charakter przewlekły, niekiedy nie ustępują po środkach rozkurczowych.…”
Section: Introductionunclassified
See 1 more Smart Citation